(untitled) (Nonconventional Technologies Review, 2022)
Within the mechatronic systems, there are interfaces for both hardware and software components. In the construction of the mechatronic system by a team, these interfaces must be considered, in order to create a system as the client wishes. The delivered system must incorporate the proposed requirements, execute them correctly, without additional unwanted functions. These interfaces must be properly tested and, depending on the complexity of the system, an appropriate method must be selected to verify and validate the system. The mechatronic system consists of mechanical, electrical and electronic elements and these are controlled by software uploaded to the system, which executes the required commands. Due to these components, the hardware and software interfaces must communicate correctly in order to perform the proposed functions. The interface is tested and validated, as are the system components. The structure of these mechatronic systems is discussed, with its elements to be considered.